The Evolution of Piano Technique and Its Impact on Modern Chinese Piano Development: A Theoretical Exploration - Wang, Qu; Jia, Haiyang (Pacific International Journal, 2023)
This paper explores the development of the piano in modern China, focusing on its role in Chinese music education, performance, and composition. With the introduction of Western music and culture, the piano gradually became an integral part of Chinese musical culture. The study investigates the factors influencing the development of the modern Chinese piano, including social history, cultural environment, and the music education system. The research employs a literature review methodology to analyze the evolution and changes in theories of modern Chinese piano development, as well as the significant theoretical perspectives and academic ideas associated with them. The study examines the historical background, cultural environment, piano performance techniques, teaching methods, and the contributions of Chinese piano composers and musicians. The findings highlight the importance of studying modern Chinese piano development theory for piano education and performance. The research aims to deepen the understanding and application of relevant theories, fostering innovation and improvement in piano art. Furthermore, the exploration of piano development theories promotes the preservation and transmission of Chinese music culture, enhances academic research, and facilitates international exchange in the field of Chinese music. The study concludes that the continuous study of technical theory is crucial for the development of the piano in China. The improvement of current technical theory serves as a catalyst for advancing Chinese piano art and strengthens the preservation and transmission of Chinese musical cultural heritage. The findings provide theoretical guidance for piano teaching and performance practice, contributing to the continuous advancement of piano art in China.